Short-Term Physiological Response of a Native Hawaiian Plant, Hibiscus arnottianus, to Injury by the Exotic Leafhopper, Sophonia orientalis (Hemiptera: Cicadellidae). Issue 2 (25th January 2019) - Avanesyan, Alina; Snook, Kirsten A; Follett, Peter A; Lamp, William O
Abstract: Sophonia orientalis (Matsumura), also known as the two-spotted leafhopper, is a widespread exotic pest of many economically important crop plants and ornamental plants in Hawaii. Sophonia orientalis is highly polyphagous and is a major threat to some of the native endemic plants. Despite the successful establishment in Hawaii, interactions of S. orientalis with its host plants remain poorly understood. Previous studies primarily focused on distribution, parasitism, and oviposition of S . orientalis in Hawaii, whereas plant physiological responses to the leafhopper's injury, and, specifically, gas exchange rates in plants, have not yet been described. In this study, we examined a short-term physiological response of a native Hawaiian plant, Hibiscus arnottianus (A. Gray), to injury by S. orientalis . We also explored whether Camellia sinensis (L.) Kuntze, a native host plant of S. orientalis in Asia, exhibits a similar response. We found that H. arnottianus plants demonstrated a rapid (2-d) physiological response to injury accompanied by 40% reduction in rate of photosynthesis and 42% reduction in rate of transpiration, whereas C. sinensis did not exhibit any reduction in gas exchange rates. We did not record any changes in plant chlorophyll levels after plant injury in either species. Our results suggest that H. arnottianus is responding to the leafhopper feeding with a generalized wound response predicted for novel plant–insect herbivore associations. We discuss potential future directions for studies which might focus on host plant responses to S. orientalis in its native versus introduced range.